Analisis Pengaruh Produksi Gabah dan Jam Kerja Terhadap Pendapatan Petani di Desa Dalung-Bali - I Wayan Adi Dana Kusuma (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2026)
Agriculture is an activity that utilizes natural resources to achieve yields, including agricultural products. Current agricultural development focuses not only on achieving high production yields but also on protecting farmers, including improving their welfare and generating income for them. Bali places great emphasis on the welfare of its people through the agricultural sector by ensuring employment opportunities for farmers, particularly in Badung Regency, Bali Province. To advance the agricultural sector, farmers need to increase their production, which is a crucial factor in supporting the success of their farming endeavours. This research aims to analyze the effects of rice (paddy) production and working hours on farmers` income in Dalung Village, North Kuta District, Badung Regency, Bali. Using a sample of 77 farmers selected through disproportionate stratified random sampling, data was collected through interviews and questionnaires. The research method used is quantitative, with descriptive analysis and multiple linear regression techniques. The result of the study show that Rice Production has a positive and significant partial effect on farmers` income, Working Hours do not have a significant partial effect on farmers` income. And simultaneously Rice Production and Working Hours have a positive and significant effect on farmers` income. This research encourages efforts to increase harvest yields through the provision of superior seeds and training, as well as promoting work efficiency among farmers. This research is expected to provide both theoretical and practical contributions. Theoretically, the results can broaden and strengthen basic knowledge regarding the influence of grain production and work hours on farmer income. Furthermore, the findings can serve as a reference for further research on similar topics. Practically, this research is expected to provide relevant and useful information for the government in formulating policies and strategies for developing the agricultural sector, particularly in efforts to improve farmer welfare in Dalung Village.